How everything works making physics out of the ordinary - Bloomfield, Louis (John Wiley & Sons , inc., 2008)
Explains the physics of approximately sixty common items, including roller coasters, elevators, television, lasers, and musical instruments, as well as nuclear weapons and reactors.